2023
DOI: 10.1044/2022_ajslp-22-00118
|View full text |Cite
|
Sign up to set email alerts
|

Speech Sound Development in 18-Month-Old Children With Sex Chromosome Trisomies

Abstract: Purpose: This study aimed to describe speech sound development in a group of 18-month-old children with sex chromosome trisomies (SCTs), compared with a group of typically developing (TD) peers. Concurrent and longitudinal relationships between speech sound abilities and lexical development were examined. Method: A group of 76 children aged 18 months, 38 children prenatally diagnosed with SCTs (12 with XXY, 12 with XYY, and 14 with XXX) and 38 TD childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
0
0
Order By: Relevance
“…In a recent publication by Johnston et al evaluating ethical principles relevant to cfDNA in SCA, they concluded that cfDNA for SCA should be universally offered to patients based on the overarching ethical principle of reproductive autonomy and emphasized that the onus of addressing the limitations of cfDNA in SCAs be placed on the providers during more comprehensive genetic counseling [ 30 ]. One possible solution to address this global debate would be pivoting from cfDNA to newborn screening for SCAs, supported by predictors of outcomes evaluated in the eXtraordinarY Babies Study and other studies evaluating early neurodevelopmental phenotypes that have resulted in evidence of risk factors and effective interventions impacting long-term outcomes for patients with SCA [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent publication by Johnston et al evaluating ethical principles relevant to cfDNA in SCA, they concluded that cfDNA for SCA should be universally offered to patients based on the overarching ethical principle of reproductive autonomy and emphasized that the onus of addressing the limitations of cfDNA in SCAs be placed on the providers during more comprehensive genetic counseling [ 30 ]. One possible solution to address this global debate would be pivoting from cfDNA to newborn screening for SCAs, supported by predictors of outcomes evaluated in the eXtraordinarY Babies Study and other studies evaluating early neurodevelopmental phenotypes that have resulted in evidence of risk factors and effective interventions impacting long-term outcomes for patients with SCA [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering language development in children with SCTs, language delays were found as early as 8 months in the production of babbling utterances (Zampini et al., 2021). Moreover, speech sound and vocabulary development delays were found at 18 and 24 months (Capelli et al., 2023; Zampini et al., 2018, 2022). In particular, nearly 70% of children with SCTs in Zampini et al.’s study (2022) were identified as LT children at 24 months.…”
Section: Introductionmentioning
confidence: 99%